Dissemination of KPC-2-Encoding IncX6 Plasmids Among Multiple Enterobacteriaceae Species in a Single Chinese Hospital - Li, Bing; Feng, Jiao; Zhan, Zhe; Yin, Zhe; Jiang, Qiyu; Wei, Ping; Chen, Xingming; Gao, Bo; Hou, Jun; Mao, Panyong; Wu, Weili; Chen, Weijun; et al. (Frontiers in Microbiology, 2018)
Forty-five KPC-producing Enterobacteriaceae strains were isolated from multiple departments in a Chinese public hospital from 2014–2015. Genome sequencing of four representative strains, namely Proteus mirabilis GN2, Serratia marcescens GN26, Morganella morganii GN28, and Klebsiella aerogenes E20, indicated the presence of blaKPC-2-carrying IncX6 plasmids pGN2-KPC, pGN26-KPC, pGN28-KPC, and pE20-KPC in the four strains, respectively. These plasmids were genetically closely related to one another and to the only previously sequenced IncX6 plasmid, pKPC3_SZ. Each of the plasmids carried a single accessory module containing the blaKPC-2/3-carrying ΔTn6296 derivatives. The ΔTn6292 element from pGN26-KPC also contained qnrS, which was absent from all other plasmids. Overall, pKPC3_SZ-like blaKPC-carrying IncX6 plasmids were detected by PCR in 44.4% of the KPC-producing isolates, which included K. aerogenes, P. mirabilis, S. marcescens, M. morganii, Escherichia coli, and Klebsiella pneumoniae, and were obtained from six different departments of the hospital. Data presented herein provided insights into the genomic diversity and evolution of IncX6 plasmids, as well as the dissemination and epidemiology of blaKPC-carrying IncX6 plasmids among Enterobacteriaceae in a hospital setting.